2011
DOI: 10.3855/jidc.1338
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of interleukin-10 gene polymorphisms and hepatitis C susceptibility in Pakistan

Abstract: Introduction: Hepatitis C virus (HCV) commonly causes a chronic infection but few of patients are able to clear the virus naturally. Interleukin-10 (IL-10) is an anti-inflammatory cytokine that can suppress the immune response against HCV. Interindividual variations in IL-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 29 publications
1
42
0
1
Order By: Relevance
“…Two genotype polymorphisms of IL-18 (137/GC and 607/CA) were associated with the outcome of HCV infection in Tunisian patients [20]. The analysis of IL-10 gene polymorphisms indicated a variation between the proinflammatory and anti-inflammatory cytokine responses, which may have resulted in immunodeficiency to HCV infection in Pakistan [21]. Meanwhile, no significant correlation has been found between SNPs of IL-10 and histological activity index in HCV patients [22].…”
Section: Introductionmentioning
confidence: 99%
“…Two genotype polymorphisms of IL-18 (137/GC and 607/CA) were associated with the outcome of HCV infection in Tunisian patients [20]. The analysis of IL-10 gene polymorphisms indicated a variation between the proinflammatory and anti-inflammatory cytokine responses, which may have resulted in immunodeficiency to HCV infection in Pakistan [21]. Meanwhile, no significant correlation has been found between SNPs of IL-10 and histological activity index in HCV patients [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analysis further showed no significant association between IL-10-819C/T (MaeIII) and IL-10 -592A/C (RsaI) polymorphisms with chronic HCV infection compared to healthy controls in Caucasian and Oriental populations [29]. By contrast, Afzal et al reported suggestive evidence of an association with hepatitis C for the IL-10 -819C/T (-592C/A) promoter polymorphism at the allele level but not in genotype distribution in a Pakistani population [33].…”
Section: Discussionmentioning
confidence: 92%
“…In previous studies, the CCG haplotype was associated with increased IL-10 production compared with the ATA and CCA haplotypes (Turner et al, 1997). In addition, Afzal et al (2011), showed that there were significant differences between HBV patients and controls in regard to ATG and CCA haplotypes. Haplotype analysis in Japanese and Chinese populations also revealed that IL-10 haplotype ATA was related to the persistent of HBV infection (Miyazoe et al, 2002;Peng et al, 2006).…”
Section: Il-10mentioning
confidence: 89%